Peran Religious Coping terhadap Quarter Life Crisis pada Mahasiswa - Sabrina Etika Utami; Hanifa Ihsani; Ane Titisemita; Sari Handayani (Journal on Education, 2023)
Quarter Life Crisis (QLC) is a crisis experienced by individuals who are entering the phase from adolescence to adulthood, or commonly referred to as the emerging adulthood phase. This crisis resulted in confusion experienced by individuals, making it unproductive in carrying out daily activities. A total of 49 students from one of the high schools in Padang City with an Islamic background became participants in this study. Data were analyzed using multiple linear regression analysis. The results of this study indicate that the hypothesis is accepted. Religious coping significantly plays a role in the QLC score. This is indicated by the calculated F value of 4.875 with a significance level of 0.012 (p <0.05). The contribution of positive and negative religious coping to the quarter life crisis score together is 17.5%. In this study it was also found that the contribution of positive religious coping only partially did not have a significant role in the quarter life-crisis. On the other hand, the contribution of negative religious coping partially remains significant in quarter life crises.